Hyperonic Stars and the Nuclear Symmetry Energy - Providência, Constança; Fortin, Morgane; Pais, Helena; Rabhi, Aziz (Frontiers in Astronomy and Space Sciences, 2019)
In the present study we analyse the effect of the density dependence of the symmetry energy on the hyperonic content of neutron stars within a relativistic mean field description of stellar matter. For the $Λ$-hyperon, we consider parametrizations calibrated to $Λ$-hypernuclei. For the $Σ$ and $Ξ$-hyperons uncertainties that reflect the present lack of experimental information on $Σ$ and $Ξ$-hypernuclei are taken into account. We perform our study considering nuclear equations of state that predict two solar mass stars, and satisfy other well settled nuclear matter properties. The effect of the presence of hyperons on the radius, the direct Urca processes, and the cooling of accreting neutron stars are discussed. Some star properties are affected in a similar way if a soft symmetry energy is considered or hyperonic degrees of freedom are included. To disentangle these two effects it is essential to have a good knowledge of the equation of state at supra-saturation densities. The density dependence of the symmetry energy affects the order of appearance of the different hyperons, which may have direct implications on the neutron star cooling as different hyperonic neutrino processes may operate at the center of massive stars. Models that allow for the direct Urca process, whether they are purely nucleonic or hyperonic ones built consistently with modern experimental data, are shown to have a similar luminosity. It is shown that for a density dependent hadronic model constrained by experimental, theoretical and observational data, the low-luminosity of SAX J$1808.4-3658$ can only be modelled for a hyperonic NS, suggesting that hyperons could be present in its core.